Autogenous Grafts for Orbital Floor Reconstruction: A review - Harish Saluja; shivani sachdeva; Semmit shah; Anuj Dadhich; Parul Tandon; Vinayak More (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Orbital fractures are relatively common midfacial injuries encountered in urban areas. Patients usually are seen with periorbitaloedema and restricted eye movements with or without changes in vision. A wide range of autogenous materials can be used in the reconstruction of orbital defects including bone grafts, cartilages and fascia each having its own strengths and weaknesses. The purpose of this paper is to provide a systematic literature review on various autogenous materials used for orbital floor reconstruction.